Impact of Covid-19 on The Aquaculture Sector Freshwater Fish Farmers in Kelantan- - Zalina Ismail; Nurfarida Jusoh; Asilah Abdul Mutalib; Zahidah Ab Latif; Shaibatul ’ Islamiah Che Man (Universitas Ahmad Dahlan, 2022)
The spread of the Covid-19 virus has affected the freshwater aquaculture industry in Malaysia. Due to this pandemic, freshwater fish products and demand decreased, followed by labor problems. Therefore, this study aims to identify freshwater farmers’ level of knowledge, perception and practices of freshwater farmers related to the Covid-19 pandemic. The study was conducted using a quantitative method to collect data. The study was conducted using an online questionnaire instrument and also survey forms were distributed to respondents in Machang, Tanah Merah and Kota Bharu. A total of 59 responses was returned. The survey was open for one month between November 15th and December 15th, 2021. The data was analysed using IBM SPPS software version 24.0 to obtain the frequency, percentage and descriptive analysis to analyse the level of knowledge, perception and practices of farmer and relationship between farmer knowledge, perception and practices about Covid-19. This study's outcome indicates that the farmer knowledge is related to farmer practices in dealing with this problem as the spread of this virus occurs rapidly. In conclusion, this research showed that the level of farmers’ knowledge, perception and practices toward Covid-19 effect is high. Directly, it will help farmers prevent the spread of this virus, helps farmers understand and be aware of Covid-19 issues and helps farmers implement good practice to reduce the risk in aquaculture activities, especially in this COVID-19 situation. This research would contribute positive impacts by finding new novel theories that can become the reference and guideline.